Hepatocyte growth factor as a driver of synovial inflammation and therapeutic resistance in rheumatoid arthritis - Dang, Quang Minh; Watanabe, Ryu; Iwasaki, Takeshi; Ishihara, Ryuhei; Kadoba, Keiichiro; Murata, Koichi; Tanaka, Masao; Ito, Hiromu; Tran, Thanh Duc; Nguyen, Sang Quang Tran; Van Nguyen, Khanh; Sun, Hongxin; et al. (Frontiers in Immunology, 2026)
BackgroundPrevious studies have demonstrated that hepatocyte growth factor (HGF) is implicated in treatment resistance in rheumatoid arthritis (RA). This study aimed to elucidate the mechanistic role of HGF in synovial inflammation and assess the therapeutic potential of targeting the HGF-c-Met axis.MethodsPlasma HGF levels were measured in 66 RA patients. The expression of HGF and its receptor, c-Met, in synovial tissue was assessed using publicly available single-cell RNA sequencing data and immunostaining. The effects of HGF on synovial fibroblasts were examined through bulk RNA sequencing, immunostaining, and quantitative PCR. The therapeutic efficacy of the c-Met inhibitor savolitinib was evaluated in a mouse model of arthritis.ResultsPlasma HGF levels were significantly elevated in RA patients (p = 0.0003) and correlated with Disease Activity Score 28-ESR (r = 0.367, p = 0.002). Single-cell analysis and immunostaining revealed that HGF was predominantly expressed in monocytes and fibroblasts, while c-Met expression was restricted to synovial fibroblasts. RNA sequencing indicated that HGF stimulation upregulated key inflammatory markers, including IL-6 and HGF itself, in synovial fibroblasts, establishing an inflammatory feedback loop. In vivo, inhibition of the HGF-c-Met pathway with savolitinib significantly suppressed arthritis development and reduced synovial inflammation. Additionally, activation of Toll-like receptor 4 and 5 activation induced HGF production in human monocytes, which may amplify IL-6-mediated inflammation.ConclusionHGF primarily acts on synovial fibroblasts, driving an IL-6-mediated inflammatory amplification loop that may contribute to therapeutic resistance in RA. Targeting the HGF-c-Met pathway could represent a novel strategy for overcoming treatment refractoriness in RA.